Pengaruh Model Pembelajaran Project Based Learning Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran IPAS Kelas IV Di MIN 2 Pontianak - Sa’diyah, Halimatus; M.Sc, Asmiati (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2025)
This study aims to determine the effect of using the Project Based Learning (PjBL) model on student learning outcomes in IPAS subjects. This research uses quantitative methods and the type of research used is quasi-experimental with the design “Nonequivalent control group design”. Data collection techniques and tools in this study are using observation sheets, test sheets and documentation. The sample in this study were 40 students of class IVD as the experimental class and 41 students of class IVE as the control class. Based on the results of data analysis, the learning outcomes obtained are the average pre-test value of 67.07 and the average post-test value of 70.49 in the control class while in the experimental class the learning outcomes are the average pre-test value of 64.75 and the average post-test value of 81.00.Based on the man whitney test, the sig. Based on the man whitney test obtained a sig value (2-tailed) of 0.000 <0.05, Ho is rejected and Ha is accepted, which means that there is an effect of using the Project Based Learning (PjBL) learning model on student learning outcomes in IPAS subjects.